Two Novel Compound Heterozygous Mutations in the TRAPPC9 Gene Reveal a Connection of Non-syndromic Intellectual Disability and Autism Spectrum Disorder - Krämer, Johannes; Beer, Meinrad; Bode, Harald; Winter, Benedikt (Frontiers in Genetics, 2021)
Introduction. Autism spectrum disorder (ASD) is characterized by deficits in communication, social interaction and repetitive behavior. Up to 70% of ASD cases are linked with intellectual disability (ID). The major genetic causes for ASD and ID are largely unknown, however a shared genetic etiology between ASD and ID must be assumed. The trafficking protein particle complex subunit 9 (TRAPPC9) is highly expressed in postmitotic neurons of the cerebral cortex, playing a key role in development. Among 43 reported cases with mutations in TRAPPC9, all (100%) showed ID and developmental delay. Among the cases including information about ASD, 26% are affected (19 cases with information, among them 5 with ASD). Nevertheless, in some cases not classified as ASD, descriptions of autistic features like hand-flapping movements are present. Clinical findings. The affected individual presented with delay of speech development. Physical development was normal Besides lateral slope of the eye-lid axis no facial abnormalities were evident. The individual was diagnosed as Intellectual disability (ID) and Autism spectrum disorder (ASD) by structured testing. Cerebral MRI revealed associated abnormalities. Genetical findings. Chromosome set was 46,XY without structural changes. Array-CGH showed a normal molecular karyotype (arr(1-22)x2,(X,Y)x1). PCR for the FMR1 gene showed 41±1 CGG repeats, and therefore no evidence for fra(X) syndrome. Panel diagnostic for syndromal ID (CASK, EP300, HIVEP2, KIF1A, TRAPPC9) revealed two structural changes in TRAPPC9 in compound heterozygosity. The mutations c.1678C>T (p.Arg560Cys) and c.3370C>T (p.Pro1124Ser) are classified as missense mutations and are both not described in literature. Conclusion. We report two new missense mutations in the TRAPPC9 gene in one individual with intellectual disability and autism spectrum disorder. The TRAPPC9 gene should be part of the diagnostic assessment in ID. ASD must be considered as a feature of TRAPPC9-associated ID. It might have been neglected in literature and should result in specific testing for ASD in affected individuals.